Ground Penetrating Radar (GPR) data on frozen lakes, Alaska, 2019-2020. - Rodrigo Correa Rangel; Andrew Parsekian (Arctic Data Center, 2020)
This dataset contains ground penetrating radar (GPR) data acquired on frozen lakes at three different regions in the North Slope of Alaska, including Utqiaġvik, Teshekpuk, and Oumalik, during April/May 2019 and January 2020, and around Fairbanks, Alaksa, during March 2020. Measurements were made using Malå ProEx 800 megahertz (MHz) (GuidelineGeo, Sundbyberg, Sweden) antennas with either single or multichannel configuration. Multichannel data were acquired using two fixed antennas configuration with internal offsets of 0.14 meters (m) (A1 and B1) and external offsets of 2.02 m (A2) and 1.74 m (B2). Raw GPR data of 29 transects from a total of 16 lakes are provided in the .RAD3 format, along with the corresponding acquisition parameters (.RAD) and Global Positioning System (GPS) coordinates (.COR) files. A spreadsheet with basic information and a Keyhole Markup Language (KML) file indicating the location of each transect are also provided. This dataset can be used to estimate snow and ice properties.